Testosterone level in seminal vesicle fluid is a better indicator of erectile function than serum testosterone in patients with prostate cancer. (18th June 2022) - Kashiwagi, Eiji; Shiota, Masaki; Naganuma, Hidekazu; Monji, Keisuke; Imada, Kenjiro; Lee, Ken; Matsumoto, Takashi; Takeuchi, Ario; Inokuchi, Junichi; Eto, Masatoshi
Abstract : Objectives: Semen comprises prostatic fluid and seminal vesicle fluid, and seminal vesicle fluid contains various factors such as prostaglandin E2 (PGE2), zinc, and testosterone, which play important roles in sperm motility. It is not known whether these factors affect erectile function. In this study, we investigated factors in seminal vesicle fluid that may affect erectile function. Methods: After receiving institutional review board approval, we collected seminal vesicle fluid samples from 134 Japanese patients with localized prostate cancer who underwent robot‐assisted radical prostatectomy. We examined the relationship between the results of the Sexual Health Inventory for Men (SHIM), erection hardness score, an original questionnaire on the presence or absence of sexual desire, and concentrations of several factors in seminal vesicle fluid (testosterone, PGE2, transforming growth factor β1, and 8‐hydroxy‐2‐deoxyguanosine), as well as the serum testosterone level. Results: Median participant age was 67 (range 51–77) years. Median concentrations were as follows: seminal vesicle testosterone 1.85 (range 0.17–4.32) ng/ml and serum testosterone 4.60 (range 1.75–10.82) ng/ml. When the SHIM score was divided into two groups, seminal vesicle testosterone concentration was significantly increased ( p  = 0.002) in participants with a SHIM score ≥17, and no significant difference was observed in serum testosterone levels ( p  = 0.661). Multivariate analysis revealed that seminal vesicle testosterone was significantly correlated with the SHIM score (≥17 vs. <17; odds ratio 2.137, 95% confidence interval 1.148–3.978, p  = 0.016). Conclusions: Testosterone levels in seminal vesicle fluid can reflect erectile function in patients with prostate cancer, suggesting that seminal vesicle testosterone is very important for male erectile function.